2009
DOI: 10.1097/pts.0b013e3181b53f6e
|View full text |Cite
|
Sign up to set email alerts
|

AHRQ's Hospital Survey on Patient Safety Culture

Abstract: Overall, the tool was shown to have moderate-to-strong validity and reliability, with the exception of the staffing subscale. The usefulness in assessing areas of strength and weakness for hospitals or units among the culture subscales is questionable. The culture subscales were shown to correlate with the perceived outcomes, but further study is needed to determine true predictive validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
5
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(141 citation statements)
references
References 11 publications
7
125
5
4
Order By: Relevance
“…The dimension "Staffing" showed a Cronbach's alpha value of 0.58, a finding also close to results presented earlier [33] where this dimension showed a value of 0.63. This dimension was also reported to exhibit similar alpha values in other studies [28,[45][46][47][48]. This means that this dimension might consist of vaguely formulated items whose importance for patient safety culture varies due to country and organization.…”
Section: Methodsological Considerationssupporting
confidence: 50%
“…The dimension "Staffing" showed a Cronbach's alpha value of 0.58, a finding also close to results presented earlier [33] where this dimension showed a value of 0.63. This dimension was also reported to exhibit similar alpha values in other studies [28,[45][46][47][48]. This means that this dimension might consist of vaguely formulated items whose importance for patient safety culture varies due to country and organization.…”
Section: Methodsological Considerationssupporting
confidence: 50%
“…Reliability testing evaluated the extent to which results obtained by the Brazilian version of HSOPSC could be replicated. In order to allow for comparison with other validation studies 11,12,13,14,15,16,17,18,19,20,21,22 , the reliability of HSOP-SC was assessed through its internal consistency as estimated using Cronbach's alpha 23,24 for each dimension or factor, in line with the dimensions proposed by the original model. Since some questionnaire items were worded positively and others negatively, negatively worded items were reverse coded so that in all cases a higher score would indicate a positive response 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Smits et al 16 obtained a model with 11 dimensions, which together explained 57.1% of the variance. After excluding the items under "Staffing", Blegen et al 21 also obtained an 11-dimension model. Bodur & Filiz 11 identified 10 dimensions of safety culture when validating the Turkish version HSOPSC, while maintaining all 42 items of the original model proposed by AHRQ.…”
Section: Discussionmentioning
confidence: 99%
“…These subscale reliabilities are somewhat lower than those of Huang et al, 19 who reported results of 0.67 to 0.73 for the same 3 subscales. Of interest, Blegen et al 44 also found low reliability scores for another validated safety culture survey. Perhaps, the measurement of safety culture requires refinement in particular settings.…”
Section: Limitationsmentioning
confidence: 99%